Engaging men and boys in the Women, Peace and Security agenda: beyond the "good men" industry - Duriesmith, David (2017)
Since the signing of United Nations Security Council Resolution 1325 (UNSCR 1325) in October 2000, there have been two explicit references to men in resolutions on the Women, Peace and Security (WPS) agenda. For the first 13 years of the agenda resolutions included men by default without naming them directly, referring to gender broadly and many particular instances of violence presumably caused by men.1 The first explicit mention appeared in 2013 in Resolution 2106, which mentioned “the enlistment of men and boys in the effort to combat all forms of violence against women.” Resolution 2106 was followed up in 2015 by Resolution 2242, which reiterated “the important engagement by men and boys as partners in promoting women’s participation in the prevention and resolution of armed conflict, peacebuilding and post-conflict situations”. These direct mentions of men within the WPS architecture limit the agenda to that of “enlisting” or “engaging” men and boys in achieving the goals of WPS, rather than a more sustained treatment of men and masculinities. While the focus on men and boys has entailed a broad effort to expand WPS to the “other side of gender”, the majority of current actions appear to follow the language within UNSCRs 2106 and 2242 by focusing on “engaging men and boys”.